Brefeldin A arrests the intracellular transport of viral envelope proteins in primary cultured rat hepatocytes and HepG2 cells. - Oda, K (1990)
We have studied the effect of brefeldin A (BFA) on the intracellular transport of the envelope proteins of vesicular stomatitis virus (VSV) and sindbis virus in primary cultured rat hepatocytes. BFA (2.5 micrograms/ml) inhibited not only the secretion of plasma proteins into the medium, but also the assembly of both G protein of VSV and E1 and E2 proteins (envelope proteins) of sindbis virus into respective virions. Concomitantly, both the acquisition of endo-beta-N-acetylglucosaminidase H resistance by the G protein and the proteolytic conversion of PE2 to E2 were found to be inhibited in the BFA-treated cells, suggesting that the intracellular transport of the envelope proteins was arrested in the endoplasmic reticulum. Such inhibitory effects of the drug were variable depending upon the culture conditions of the hepatocytes. In the 1-day-cultured cells, even in the presence of the drug, newly synthesized envelope proteins were assembled into the virions after a 3 h chase period, at the same time as secretion of plasma proteins into the medium resumes. In contrast, in 4-day-cultured hepatocytes, BFA continuously blocked the entry of the envelope proteins into the virions and the release of plasma proteins into the medium for at least 5 h. BFA also completely inhibited the exocytotic pathway in HepG2 cells. These results indicate that the duration time of the effect of BFA is different from one cell to another and may change depending upon the culture conditions of the cells.